2020
DOI: 10.1042/cs20200923
|View full text |Cite
|
Sign up to set email alerts
|

The PAR-1 antagonist vorapaxar ameliorates kidney injury and tubulointerstitial fibrosis

Abstract: Protease-activated receptor (PAR)-1 has emerged as a key profibrotic player in various organs including kidney. PAR-1 activation leads to deposition of extracellular matrix (ECM) proteins in the tubulointerstitium and induction of epithelial-mesenchymal transition (EMT) during renal fibrosis. We tested the anti-fibrotic potential of vorapaxar, a clinically approved PAR-1 antagonist for cardiovascular protection, in an experimental kidney fibrosis model of unilateral ureteral obstruction (UUO) and an AKI-to-CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 67 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…The excessive accumulation of ECM is another important feature of tissue or renal fibrosis. Several previous studies have reported the increases of main ECM components, including collagens, fibronectin and proteoglycans in renal interstitial fibrotic tissues 76 , 77 . In addition, in vitro studies have demonstrated that α-SMA-expressing renal fibroblasts promote the synthesis of ECM components, including collagen type I and fibronectin 65 , 78 .…”
Section: Discussionmentioning
confidence: 93%
“…The excessive accumulation of ECM is another important feature of tissue or renal fibrosis. Several previous studies have reported the increases of main ECM components, including collagens, fibronectin and proteoglycans in renal interstitial fibrotic tissues 76 , 77 . In addition, in vitro studies have demonstrated that α-SMA-expressing renal fibroblasts promote the synthesis of ECM components, including collagen type I and fibronectin 65 , 78 .…”
Section: Discussionmentioning
confidence: 93%
“…The EMT process is controlled by a network of signalling pathways such as transforming growth factor (TGF)-β/Smad and Hippo pathways, and is executed by a subset of transcription factors including ZEB1/2, Snail/Slug, Twist, and YAP/TAZ [ 28 , 61 , 64 69 ]. Previous studies have reported that PAR-1 activation contributes to renal EMT and interstitial fibrosis during chronic obstructive nephropathy [ 70 , 71 ]. Pharmacological inhibition of PAR-1 provides a renoprotective strategy by virtue of its anti-fibrotic effects, mediated partly via inhibition of Smad-dependent TGF-β signalling [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that PAR-1 activation contributes to renal EMT and interstitial fibrosis during chronic obstructive nephropathy [ 70 , 71 ]. Pharmacological inhibition of PAR-1 provides a renoprotective strategy by virtue of its anti-fibrotic effects, mediated partly via inhibition of Smad-dependent TGF-β signalling [ 71 ]. In gastric and CRC cells, PAR-1 activation leads to upregulation of pro-EMT transcriptional factor Snail and Twist, respectively [ 28 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-466i and miR-466k are sponged by circRNA-Kcnq1ot1 participate in cardiomyocytes apoptosis in acute myocardial infarction [ 29 ]. By analyzing the ceRNA results, we reveal that the up-regulated circRNA-3109 or circRNA-14838 is able to suppress miR-615-5p, which binds to collagen I, may promote renal fibrosis [ 30 ]. Furthermore, it is reasonable to assume that the dysregulated circRNA-2862 may sponge with miRNA-709, circRNA-6671 with miRNA-3473, circRNA-6471 with miRNA-466 and relieve their suppression to downstream target may participate in the process of kidney injured by UUO.…”
Section: Discussionmentioning
confidence: 99%